Trends in body image of adolescent females in metropolitan and non-metropolitan regions: a longitudinal study. (December 2016) - Craike, M.; Young, J.; Symons, C.; Pain, M.; Harvey, J.; Eime, R.; Payne, W.
Abstract Background Body dissatisfaction is associated with a range of adverse outcomes, including impaired psychological health, low physical activity and disordered eating. This longitudinal study used the Factors Influencing Transitions in Girls' Active Leisure and Sport (FITGALS) dataset to examine trends in body image of adolescent females. Specifically, the study examined satisfaction with body size, physical appearance and dieting behaviour for two cohorts at transitional life phases in two geographic regions longitudinally over a 3-year period. Methods A sample of 732 adolescent females in Grade 7 (n  = 489, 66.8 %) and Grade 11 (n  = 243, 33.2 %) at randomly selected Australian metropolitan and non-metropolitan secondary schools responded to a questionnaire in three successive years from 2008 to 2010. Participants reported perceptions about their body size and physical appearance and whether they were, or ought to be, on a diet. The data were analysed using a series of longitudinal logistic regression models. Results Dieting and dissatisfaction with body size significantly increased over time and more so for older than younger girls. Region significantly moderated the effect of grade level regarding dissatisfaction with body size but not dieting. In non-metropolitan regions, those in the younger cohort were significantly more likely to be dissatisfied with their body size than the older cohort; whereas in metropolitan regions, those in the older cohort were significantly more likely to be dissatisfied with their body size than the younger cohort. Adolescent female's perceptions of their appearance were unchanged over time, region and grade level. Conclusions Differences across time, region and grade level were found among adolescent females on body size and dieting behaviour, but not physical appearance. Adolescent females experience early and increasing body size dissatisfaction and dieting as they age, but stable perceptions of physical appearance. Age and geographic region are important considerations for the timing and targeting of interventions to address body image concerns. Further investigation of regional differences in body image perceptions and factors that affect these is warranted. The findings of this study highlight the ongoing need for strategies during adolescence to promote a healthy appreciation of body size and appearance.